2021
DOI: 10.1016/j.bpj.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Krokinobacter rhodopsin 2 Kinetics

Abstract: We investigated the temperature-dependent kinetics of the light-driven Na þ pump Krokinobacter rhodopsin 2 (KR2) at Na þ -pumping conditions. The recorded microsecond flash photolysis data were subjected to detailed global target analysis, employing Eyring constraints and spectral decomposition. The analysis resulted in the kinetic rates, the composition of the different photocycle equilibria, and the spectra of the involved photointermediates. Our results show that with the temperature increase (from 10 to 40… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…We also studied the photocycle kinetics of Er NaR on the ns to s timescale under various conditions using flash photolysis. At pH 8.0, the photocycle, as well as the impact of different sodium concentrations on the Er NaR, are similar to what was observed for KR2 1 , 28 , 29 . The K 1 -intermediate at the end of the ultrafast measurement (1.8 ns), remains present at the beginning of the flash photolysis time scale (450 ns), showing that K 1 is populated throughout the ns timescale and no photocycle intermediate is missed due to the experimental time gap (Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…We also studied the photocycle kinetics of Er NaR on the ns to s timescale under various conditions using flash photolysis. At pH 8.0, the photocycle, as well as the impact of different sodium concentrations on the Er NaR, are similar to what was observed for KR2 1 , 28 , 29 . The K 1 -intermediate at the end of the ultrafast measurement (1.8 ns), remains present at the beginning of the flash photolysis time scale (450 ns), showing that K 1 is populated throughout the ns timescale and no photocycle intermediate is missed due to the experimental time gap (Fig.…”
Section: Resultssupporting
confidence: 78%
“…K 1 decays within the early µs-range (lifetime distribution in the range of 5–10 µs) to form the K 2 -intermediate. This intermediate state is considered to be K-like because of the more pronounced red-shift compared to the known L-intermediates of other microbial rhodopsins 28 , 29 . The transition to the blue-shifted M-intermediate then occurs within ~1 ms.…”
Section: Resultsmentioning
confidence: 99%
“…We also studied the photocycle kinetics of Er NaR on the ns to s timescale under various conditions using flash photolysis. At pH 8.0, the photocycle, as well as the impact of different sodium concentrations on the Er NaR, are similar to what was observed for KR2 1,30,31 . The K 1 -intermediate at the end of the ultrafast measurement (1.8 ns), remains present at the beginning of the flash photolysis time scale (450 ns), showing that K 1 is populated throughout the ns timescale and no photocycle intermediate is missed due to the experimental time gap (Fig.…”
Section: Resultssupporting
confidence: 78%
“…K 1 decays within the early µs-range (lifetime distribution in the range of 5-10 µs) to form the K 2 -intermediate. This intermediate state is considered to be K-like because of the more pronounced red-shift compared to the known L-intermediates of other microbial rhodopsins 30,31 . The transition to the blue-shifted M-intermediate then occurs within ~1 ms.…”
Section: Spectroscopy Of Ernarmentioning
confidence: 99%
“…Therefore, we concluded that both intermediates are populated simultaneously. Such a feature is common for microbial rhodopsins and was observed various times in the past. On the late microsecond to early millisecond time scale, another red-shifted photocycle intermediate P 5 is formed, which decays to form the final photocycle intermediate P 6 at ∼10 ms. Ultimately, the protein recovers its parent state after ∼6 s. Intermediates P 5 and P 6 are considered to be especially spectrally similar.…”
mentioning
confidence: 85%